ANALISIS KUALITAS LAYANAN SANGGAR KEGIATAN BELAJAR TAHUN PEMBELAJARAN 2008-2009 DI KABUPATEN SITUBONDO - Minarso, Christinia (JIV-Jurnal Ilmiah Visi, 2009)
Learning Activity Center (LAC) provides the local community with several kinds of educational services. The existence of the LAC is appricated on the basis of the benefits the community gained and the quality of the services often comes up as a problem. This research aimed at assessing the quality of educational services provided by LAC in Situbondo District along the academic year of 2008 – 2009. To measure the service quality SERVQUAL model was employed and the research population covered Package A, B, and C participants, attendants of cources, the participants of functional litracy programs, and the parents of early childhood education. The measurement covers reliability of the services, sensitivity, assurance, and emphaty. The result of the study shows some weakness in the services to improve later aside from the positive achievement.